Carbonic anhydrase IX-directed immunoliposomes for targeted drug delivery to human lung cancer cells in vitro - Wong BCK; Zhang H; Qin L; Chen H; Fang C; Lu A; Yang Z (Dove Medical Press, 2014)
Blenda Chi Kwan Wong,1 Hongqi Zhang,1 Ling Qin,2 Hubiao Chen,1 Chen Fang,1 Aiping Lu,1 Zhijun Yang1 1School of Chinese Medicine, Hong Kong Baptist University, Kowloon Tong, Kowloon, Hong Kong; 2Department of Orthopaedics and Traumatology, The Chinese University of Hong Kong, Prince of Wales Hospital, Shatin, New Territories, Hong Kong Abstract: Targeted drug delivery to cancer cells by use of antibody-conjugated liposomes (immunoliposomes) has attracted considerable interest in recent years. Despite increasing efforts in developing immunoliposomes as drug carriers, the investigation of useful tumor-associated antigen targets is far from complete. Carbonic anhydrase IX (CA IX) is a cell surface antigen characterized by hypoxia-induced expression in many solid tumors. This study investigated the feasibility of CA IX-directed immunoliposomes for targeted delivery of docetaxel to human lung cancer cells in vitro. Docetaxel-loaded immunoliposomes targeting CA IX were developed with an encapsulation efficiency of 84.4±3.9% and an average particle size of 143.9±11.1 nm. Using fluorescence-based flow cytometry, the in vitro binding activity of the immunoliposomes was found to be significantly higher (by 1.65-fold) than that of the nontargeted liposomes in CA IX-positive lung cancer cells, whereas no such difference was observed between the two groups when CA IX was not expressed. Furthermore, immunoliposomal docetaxel exhibited the strongest growth inhibitory effect against CA IX-positive lung cancer cells when compared with nontargeted liposomal docetaxel or free docetaxel solution. These data suggested that CA IX-directed immunoliposomes could serve as a promising drug delivery system for targeted killing of lung cancer cells. Keywords: cancer chemotherapy, conjugation, liposome, nanotechnology, cell surface antigen, hypoxia